PROSPECTIVE STUDY OF TRAGAL PERICHONDRIUM VERSUS TEMPORALIS FASCIA AS GRAFT FOR TYMPANOPLASTY - Bahuguna, Deepti Pandey (Innovare Journal of Medical Sciences, 2016)
ABSTRACT Objective: Relative merit of materials and associated techniques for myringoplasty makes important study perspective of clinical relevance and evidence based practice. Methods: Prospective study of outcomes in myringoplasty using either temporalis fascia or tragal perichondrium in 23 adult patients of tympanic perforation is reported.2 months after surgery pure tone audiometry and tympanic membrane examinations were performed. Parameters observed were survival and uptake of graft and hearing improvement in terms of average air-bone gap. Results and Conclusion: Temporalis fascia graft is marginally superior.However near comparable outcomes with tragal perichondrium graft make it a choice option for cases with negative middle ear pressure with Eustachian tube dysfunction and large perforations Cartilage is more robust and unlikely to undergo retraction. Keywords: Atelactic ear, Myringoplasty, Tragal prichondrium, Tympanic perforation.